Direct estimation of ethanol as a negative peak from alcoholic beverages and fermentation broths by reversed phase-HPLC. Issue 23 (31st May 2016) - Nisha, M.; Shankar, Mukund; Krishnan, Nagasathiya; Saleena, Lilly M.; Rajesh, Mathur; Vairamani, M.
Abstract : Direct injection of alcoholic samples/broths into a RP-HPLC (with a PDA-UV detector) system to quantify ethanol directly as a negative peak. The kind of peak pair depends on the ethanol concentration as described in the article. Abstract : A relatively simple and straightforward technique utilizing reversed phase liquid chromatography with a PDA-UV detector was used for the detection and quantification of ethanol. Samples of alcoholic beverages and fermentation broths were injected without any prior chemical pre-treatment or structural modification. The C18 column was equilibrated with water as a mobile phase having a high UV absorbing compound, acetone, added in an optimized percentage. Ethanol when injected resulted in a negative peak within 4 minutes of runtime, and the absolute area/height of the peak was used for quantification. The method was validated for linearity with the detection ranging from 0.1–100% v/v. Intra-day and inter-day precision experimental results were within acceptable limits. The accuracy and repeatability of this method can reduce the dependency of using specific columns and detectors for the analysis of ethanol.